Efektivitas Teknik Reward dan Punishment dalam Konseling Kelompok Untuk Meningkatkan Self Control dalam Mengurangi Kecanduan Game Online pada Siswa Sekolah Kejuruan - Kase, Olfi Irene; Lay, Andriyani E; Abel, Rizky M A (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
Addiction to online games has become a significant global problem in recent years, affecting several teenagers. Online game addiction is caused by various aspects, one of which is low self-control in individuals. The problem in this study is the high level of online game addiction in students. The purpose of this study was to determine the effectiveness of the application of group counseling using reward and punishment techniques to increase self-control in reducing students' online game addiction. This type of research is quantitative using experimental method type one group pretest- postest design. The population in this study was class X students at SMK Negeri 2 Kupang City, totaling 32 people. The research sample was 8 students. The sample was determined by purposive sampling technique. Measuring instruments in this study used scales and questionnaires. The data analysis technique used is descriptive analysis technique and T test. Before being given treatment, the level of addiction to online game addiction was in the very high and high categories, and the level of self-control was in the medium and low categories. After being given treatment, the results showed that group counseling with reward and punishment techniques can effectively increase self-control in reducing students' online game addiction as shown by the T test analysis of the results of t count 213.76> t table 69.788 online game addiction and t count 100.44> t table 20.125 self-control with a significance level of 0.5. It is concluded that the reward and punishment technique in group counseling is quite effective in increasing self-control in reducing students' online game addiction. But it can be considered in a longer technique intervention time and continuous monitoring after treatment.